Kinetics and Equilibrium Studies on the Sorption of Manganese(II) and Nickel(II) onto Kaolinite and Bentonite - B. Sathyanarayana; K. Seshaiah (E-Journal of Chemistry)
The sorption of manganese(II) and nickel(II) onto two adsorbents, kaolinite and bentonite from aqueous solution was studied in batch mode. Effect of pH, contact time, adsorbent dose, and initial metal ion concentration on adsorption was investigated. The adsorbents exhibit good sorption potential for manganese(II) and nickel(II) with a peak value at pH 5 and pH 6 respectively. More than 70% sorption occurred within 20 min for manganese(II) and nickel(II) and equilibrium was attained at 90 min. for manganese(II) and 120 min for nickel(II). Freundlich and Langmuir's mathematical models were used to describe batch adsorption. The adsorption was found to be favourable with respect to both the isotherms. The adsorption of the two metal ions from aqueous solution onto two adsorbents followed pseudo-second order kinetics.